O império de papel: no labirinto das discórdias, denúncias, cartas e representações contra os governadores da capitania de Goiás c. 1749 – c. 1804 - Pereira, Alan Ricardo Duarte (2020)
Ruling overseas was not, by far, merely a task confined to the unrestricted obedience of the vassals residing in the spaces of conquest. Nor was it enough to display the titles of nobility and privileges for display, then, as a representation of the king. To occupy the position of governor and captain-general in the different parts of the Portuguese Empire demands more than that. The work that the developers try to analyze just as it shows the aspect: as government and management practices in the Capitânia de Goiás between 1749 and 1804. Thus, since the study of letters, complaints and criticisms addressed to the governors. In such a way that governors, ministries, potential sites and charters are, in short, the focus of our work. Conceptually, we divided our study into two moments. The first moment, from 1749 to 1778, is analyzed based on the concept of illicit acts. In general, they are criticism talking about theft, corruption, embezzlement, the golden misfits, or other involving the Vila Boa Foundry and the Royal Treasury of Goiás. The second, in turn, starts in 1778 and goes until 1804. During this period, governors were studied from the concept of jurisdictional issues. The content of the criticism refers to the actions of governors that do not go beyond their jurisdiction, a usurpation of functions, arrests and persecutions. In view of this, the Paper Empire was a way to study the performance of the governors of the Goias Captaincy and thus show a centrality of representations and denunciations in the reproduction of governance overseas.